PARENTING STYLE AND HOME EDUCATION TRANSFORM HUMAN DEVELOPMENT - Wijayanti, Laksmi Mayesti; Tukiran, Martinus; Santoso, Priyono Budi; PURWANTO, AGUS; Hyun, Choi Chi; Asbari, Masduki (Journal of Industrial Engineering & Management Research, 2020)
- Parenting style undoubtedly has influenced the outcome of children and young adults psychological wellbeing and academic achievement. This review article highlights three research papers regarding parenting style and its implications on human development. The aforementioned parenting styles include Authoritarian, Permissive/indulgence, Authoritative and Neglective. All of the research papers using quantitative methods empirically proved that parenting style and home education have positively influenced human development. These articles provide a thorough description of parenting style correlated with the adolescent outcome. This review paper divided into a summary of each research paper followed by a brief analysis on each study. The final section will include the comprehensive analysis on the three papers and its recommendation on the field of human development.